College algebra - Parreño, Elizabeth B. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2011)
This book is intended for Filipino college students. The first chapter deals with a review of the topics in basic mathematics and elementary algebra such as set theory, operations and properties of real numbers, exponents, and polynomials.
1. Introduction -- 2. Linear equations -- 3. Inequalities -- 4. Special products and factoring polynomials -- 5. Radicals -- 6. Quadratic Equations -- 7. Functions.
Includes bibliographical references.
Keywords: ALGEBRA -- MATHEMATICS